An Implementation Method for Distributed Object-Oriented Applications - Alves, Vander; Borba, Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2001.23987, 2001)
Distribution has become an essential non-functional requirement of most applications. The same application may be required to use different distribution platforms simultaneously or during its evolution. However, distributed applications are considerably more difficult to design, implement and test than centralized systems even with the same functionality. We present an implementation method which guides the progressive transformation of an initially centralized application into a distributed one. The method helps to tame the inherent complexity of distributed systems and makes tests more effective. Additionally, it relies on a design pattern promoting extensibility and reuse of other layers such as the user interface and the business layers.